Experimental Study on the Influence of Microbial Content on Engineering Characteristics of Improved Expansive Soil - Ouyang, Qianwen; Xiao, Hongbin; Li, Zhenyu; Jiang, Weichang; Su, Huanyu; Tian, Xuwen; Ouyang, Miao (Frontiers in Earth Science, 2022)
In order to study the influence of microbial content on the engineering properties of expansive soil im-proved by microbially induced calcium carbonate (MICP) method, and to clarify its influence law and mechanism of action, and to provide some theoretical reference for the application of MICP method to expansive soil treatment. Microbial reproduction and their mineralization in expansive soils have been studied. The problems such as moisture content controlling and low calcium content in the process of treating expansive soil with MICP method have been solved by means of adding calcium salt and using optimum moisture content as the control standard of the total amount of bacterial solution and cementation solution. The tests such as compaction, swelling rates and triaxial shear are carried out. The hydrophilicity, compaction, expansibility and strength characteristics of improved expansive soil under different microbial content are analyzed. The results demonstrate that with the increasing of microbial content, the dry density and shear strength of the improved soil are first increased significantly and then tend to be stable gradually. At the same time, the hydrophilicity and expansibility of improved soil are all decreased significantly. The microstructures of improved expansive soil are imaged by scanning electron microscope. Analytic results show that soil particles have been cemented and the pores in the soil have been filled due to microbially induced calcite precipitation. As a result, microstructure characteristics of the soil have been improved. From the microscopic point of view, the improvement mechanism of MICP method on expansive soil has been revealed. The conclusions above laid a theoretical foundation for in-tensive study on the improvement of expansive soil by MICP method. It also provides a new idea for perfecting and expanding the engineering application of expansive soil improvement technology.